Stochastic Consumption, Risk Aversion, and the Temporal Behavior of Asset Returns - Hansen, Lars Peter; Singleton, Kenneth J. (Journal of Political Economy, 1983)
This paper studies the time-series behavior of asset returns and aggregate consumption. Using a representative consumer model and imposing restrictions on preferences and the joint distribution of consumption and returns, we deduce a restricted log-linear time-series representation. Preference parameters for the representative agent are estimated and the implied restrictions are tested using postwar data.